Pembuatan Program Home-Based Childcare Untuk Stimulasi Perkembangan Kognitif Anak Usia Dini - Hardiyanti, Siti; Ana, Ana; Rinekasari, Nenden Rani (Prodi PKK - Departemen PKK - Universitas Pendidikan Indonesia, 2019)
This research was conduct due to the absence of a program in childcare with a focus stimulation for cognitive development, this program is created Home-Based Childcare with the development of childcare characteristics by Barnados (2017) such as care in an environment that’s like home, flexibility for child and family, nurturing relationships and attention to individual needs. A Design Based Research (DBR) was used to collect data from three participants compiring early childhood education experts, family education experts and childcare practitioners in two times judgment. The results represent that at first times judgment program was designed to be in decent category with revisions on program purpose, program activity planning, process management activities and program activity reports. Futhermore in second times judgment indicates that the program is in very decent category. Therefore the program can be used in childcare to stimulate for children cognitive development. The results recommend to childcare manager, that a home-based childcare program that has been created by researchers can be implemented in childcare, as well as for future researchers, conducting research with a topic of report the children developing aspects of the digital-based program activities.